A Randomized Controlled Trial on Functional Relaxation as an Adjunct to Psychoeducation for Stress - Lahmann, Claas; Gebhardt, Maria; Sattel, Heribert; Dinkel, Andreas; Pieh, Christoph; Probst, Thomas (Frontiers in Psychology, 2017)
This randomized controlled trial investigated whether adding the psychodynamically based body-oriented psychotherapy “Functional Relaxation” (FR) to psychoeducation (PE) is more effective than PE alone to reduce stress and stress-associated complaints. Eighty-one participants with elevated stress-levels, ≥50 points on the global scale of the Perceived Stress Questionnaire (PSQ), received either 10 sessions of manualized FR+PE (n=42) or 2 sessions of manualized PE alone (n=39) in a group setting. Six FR trainers took part in this study. Stress-level was the primary outcome and secondary outcomes were depression and somatization. Multilevel models for discontinuous change revealed that FR+PE was more helpful to reduce stress-levels than PE from baseline to end of intervention (t0t1) as well as from baseline to 6-months after baseline (t0t2) (both p<.05) with effect sizes (d) being medium for PE (dt0t1=.57; dt0t2=.67) and large for FR+PE (dt0t1=1.59; dt0t2=1.42). Moreover, FR+PE affected depression and somatization more positively than did PE from t0 to t1 as well as from t0 to t2 (all p<.05). Effect sizes for depression were small to medium for PE (dt0t1=.52; dt0t2=.37) and large for FR+PE (dt0t1=1.04; dt0t2=.95). Effect sizes for somatization were small for PE (dt0t1=.18; dt0t2=.19) and medium to large for FR+PE (dt0t1=.73; dt0t2=.93). In summary, the combination of FR and PE was more effective than PE alone. The results of the present trial provide first evidence that FR might be a potent component of stress interventions. Adding FR to such interventions might better help prevent clinically relevant disorders such as depression or somatization.